Application of Business Law: Business Monopoly, Rule Violation and Environmental Damage - Setyo Widodo, Djoko (Journal of Law, Politic and Humanities, 2021)
This study discusses the application of business law: business monopoly, violation of rules and environmental damage. Business law is intended to regulate and control the behaviour of organizations or business people. The existing law can form excellent and healthy company activities and have a good impact on employees, the company, and the surrounding environment. In this study, the researcher used descriptive qualitative and library research methods by reviewing previous articles that were relevant to this research. The results of this study are: 1) Business Monopoly is related to Business Law, 2) Rules violation is related to Business Law, and 3) Environmental Damage is related to Business Law.